In situ T-cell transfection by anti-CD3-conjugated lipid nanoparticles leads to T-cell activation, migration, and phenotypic shift. (February 2022) - Kheirolomoom, Azadeh; Kare, Aris J.; Ingham, Elizabeth S.; Paulmurugan, Ramasamy; Robinson, Elise R.; Baikoghli, Mo; Inayathullah, Mohammed; Seo, Jai W.; Wang, James; Fite, Brett Z.; Wu, Bo; Tumbale, Spencer K.; et al.
Abstract: Ex vivo programming of T cells can be efficacious but is complex and expensive; therefore, the development of methods to transfect T cells in situ is important. We developed and optimized anti-CD3-targeted lipid nanoparticles (aCD3-LNPs) to deliver tightly packed, reporter gene mRNA specifically to T cells. In vitro, targeted LNPs efficiently delivered mCherry mRNA to Jurkat T cells, and T-cell activation and depletion were associated with aCD3 antibody coating on the surface of LNPs. aCD3-LNPs, but not non-targeted LNPs, accumulated within the spleen following systemic injection, with mCherry and Fluc signals visible within 30 min after injection. At 24 h after aCD3-LNP injection, 2-4% of all splenic T cells and 2-7% of all circulating T cells expressed mCherry, and this was dependent on aCD3 coating density. Targeting and transfection were accompanied by systemic CD25 +, OX40 +, and CD69 + T-cell activation with temporary CD3e ligand loss and depletion of splenic and circulating subsets. Migration of splenic CD8a + T cells from the white-pulp to red-pulp, and differentiation from naïve to memory and effector phenotypes, followed upon aCD3-LNP delivery. Additionally, aCD3-LNP injection stimulated the secretion of myeloid-derived chemokines and T-helper cytokines into plasma. Lastly, we administered aCD3-LNPs to tumor bearing mice and found that transfected T cells localized within tumors and tumor-draining lymph nodes following immunotherapy treatment. In summary, we show that CD3-targeted transfection is feasible, yet associated with complex immunological consequences that must be further studied for potential therapeutic applications.